Thirty years of Ukrainian Antarctic Research: Assessing the National Antarctic Program’s institutional achievements within the Antarctic Treaty System - E. Dykyi; D. Cheberkus; A. Fedchuk; O. Pnyovska; V. Malanchuk (Ukrainian Antarctic Journal, 2023)
Ukraine made a significant contribution to the study of the Antarctic. People from Ukraine were part of the expeditions that discovered and explored the Antarctic and conquered the South Pole in the XIX – beginning of the XX century. From the end of the 1950s to the beginning of the 1990s, Ukrainian researchers and engineers made valuable efforts to establish and develop Soviet Antarctic expeditions. With the acquisition of independence, the difficult and ambitious path of studying the Antarctic under the flag of Ukraine began. This article provides a historical overview of the main institutional achievements in the development of Ukrainian Antarctic research from 1993 to the present. Also, it outlines the current state, challenges, and prospects for further developing Ukraine’s National Antarctic Program within the Antarctic Treaty System. The gradual development of the State Special-Purpose Antarctic Research Programs is noted, and the main results are presented. The scientific potential and contribution to international scientific cooperation of Ukraine’s key Antarctic infrastructure facilities are revealed – Vernadsky station as a multi-purpose observatory for monitoring geophysical processes and the impact of climate change on the Antarctic ecosystems, and the ice-capable research vessel Noosfera. It is shown that the environmental protection initiatives and measures developed by Ukraine to regulate tourist activities are an important contribution to the development of the international legal regime of Antarctica.